Overview of Clinical Progress in Pulmonary Ground-glass Nodules - Lei LI; Dan LIU; Yingying ZHU; Weimin LI (Chinese Journal of Lung Cancer, 2016)
Ground-glass nodules (GGNs) was a special type of pulmonary nodules. With the progress of high resolution CT (HRCT), it achieved a higher positive rate and attracted much attention in recent years. For lacking characteristic symptoms, the early diagnosis of lung cancer was difficult even nowadays. However, it had been proved that GGNs was well associated with lung cancer in previous studies. Therefore, optimized managements of GGNs could help diagnosis and treatments of lung cancer at early stage. In this review, we summarized the definition, classification, imaging characteristics, growing history, molecular pathological features and suggested managements of GGNs.